2007
DOI: 10.1029/2007pa001504
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to dissolution correction of Mg/Ca–based paleothermometry in the tropical Pacific

Abstract: [1] Mg/Ca in planktonic foraminifers carries two main signals: calcification temperature and postdepositional test dissolution. Shell dissolution thus distorts water temperature reconstructions made with Mg/Ca in foraminifers. This problem could be resolved by quantifying the impact of carbonate dissolution on Mg/Ca with an independent, temperature-insensitive deep-sea calcite dissolution proxy, such as the Globorotalia menardii fragmentation index (MFI). To test the validity of this approach, we measured Mg/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 57 publications
2
44
0
Order By: Relevance
“…In the eastern North Atlantic Schiebel et al (1997) restricted this to the upper 60 m -consistent with pump and plankton tow data from our study area in July-August 1994 (M. R. Chapman, unpublished data). Mg/Ca studies of G. bulloides suggested that the best relationship between G. bulloides Mg/Ca ratios and temperature is at 30 m water depth (Mekik et al, 2007), further confirming the near surface preference of this species. The present day hydrography at the core site (SST range of~8°C in February to~12°C in August) match closely the idealised temperature window for this spring-summer species, suggesting that, unless maximum temperatures fall below the 8°C threshold, we are unlikely to have any problems with periods of reduced or no productivity over the Holocene sequence of our record.…”
Section: Species Ecology and Distributionmentioning
confidence: 80%
See 1 more Smart Citation
“…In the eastern North Atlantic Schiebel et al (1997) restricted this to the upper 60 m -consistent with pump and plankton tow data from our study area in July-August 1994 (M. R. Chapman, unpublished data). Mg/Ca studies of G. bulloides suggested that the best relationship between G. bulloides Mg/Ca ratios and temperature is at 30 m water depth (Mekik et al, 2007), further confirming the near surface preference of this species. The present day hydrography at the core site (SST range of~8°C in February to~12°C in August) match closely the idealised temperature window for this spring-summer species, suggesting that, unless maximum temperatures fall below the 8°C threshold, we are unlikely to have any problems with periods of reduced or no productivity over the Holocene sequence of our record.…”
Section: Species Ecology and Distributionmentioning
confidence: 80%
“…Mekik et al (2007) suggest that surface dwelling species, and G. bulloides in particular, are far less susceptible to such effects and exhibit no significant dissolution. They concluded that G. bulloides was therefore a species that had the potential to provide a pure temperature signal in its Mg/Ca ratio.…”
Section: Species Ecology and Distributionmentioning
confidence: 95%
“…U/Ca and Mg/Ca in G. sacculifer are also decreased (by $30% and $18%, respectively) at Ceara Rise, but changes at OJP are less clear for this species (Russell et al, 1994;Brown and Elderfield, 1996). The decrease in element/Ca ratios is probably caused by heterogeneous distributions of elements in shells and preferential dissolution of shells and parts enriched with these elements in under-saturated deep waters (Russell et al, 1994;Brown and Elderfield, 1996;Rosenthal et al, 1997;Fehrenbacher et al, 2006;Mekik and Franc ßois, 2006;Mekik et al, 2007). In this study, the two dissolution affected samples are not included in Figs.…”
Section: Dissolution Effect On U/camentioning
confidence: 84%
“…Also, differential partial planktonic foraminifera test dissolution can have modulated the amplitude of SST changes in this region, which is known to be particularly corrosive (Mekik et al, 2007). For example, an increase in primary productivity over the Holocene would necessarily have increased biologically-mediated calcite dissolution over this time period, potentially leading to decreased Mg/Ca-derived SST estimations.…”
Section: Mg/ca-derived Sst Trends During the Holocenementioning
confidence: 99%